A Facile Synthesis of 3‐(Arylthio)imidazo[1, 2‐a]pyridin‐2(3H)‐ones from 2‐Aminopyridinium Bromides and Sodium Arenesulfinates. Issue 45 (23rd November 2020) - Saroj,; Rangan, Krishnan; Kumar, Anil
Abstract : A simple and convenient method has been developed for the synthesis of 3‐(arylthio)imidazo[1, 2‐ a ]pyridin‐2(3H)‐ones through a catalyst‐free reaction of 2‐aminopyridinium bromides with sodium arenesulfinates. A variety of 3‐(arylthio)imidazo[1, 2‐ a ]pyridin‐2(3H)‐ones were obtained in moderate to excellent (33–85 %) yields. The developed protocol is operationally simple, exhibits a broad substrate scope with a wide range of functional groups, and is amenable for gram‐scale synthesis. Abstract : Synthesis of 3‐(arylthio)imidazo[1, 2‐ a ]pyridin‐2(3H)‐ols has been achieved through a catalyst‐free, one‐pot reaction of 2‐aminopyridinium bromides with sodium arenesulfinates. The tandem reaction involved intramolecular amidation followed by sulfenylation and afforded a wide range of 3‐(arylthio)imidazo[1, 2‐ a ]pyridin‐2(3H)‐ols in moderate to excellent (33–85 %) yields. The method exhibited broad substrate scope with a wide range of functional group tolerance, and is amenable for gram‐scale synthesis.